Cholecystitis secondary to Salmonella typhi: a rare pathology with an unreported management option-a case report and literature review - Michael Ghio; Angelle Billiot; Jessica A. Zagory; Mary L. Brandt (SpringerOpen, 2022)
Abstract Background This report describes the presentation and course of treatment for one of the youngest reported cases of empyema of the gallbladder. Given the rare occurrence of this disease process, we elected to proceed with a systematic review of the literature. This is only the 7th case series discussing pediatric empyema of the gallbladder due to Salmonella typhi in the literature, and the second case ever reported in the USA. Case presentation We report a case of a previously healthy 13-month-old girl who presented with diffuse peritonitis and equivocal imaging studies. Diagnostic laparoscopy revealed purulent peritonitis. The gallbladder was distended with intraluminal pus. Laparoscopy was converted to laparotomy to facilitate exposure, and a cholecystostomy tube was placed. Cultures from the fluid were positive for Salmonella typhi. The patient received a 14-day course of intravenous Ceftriaxone followed by 14 days of oral amoxicillin and clavulanate. A cholangiogram performed 8 weeks after surgery confirmed normal biliary anatomy. The cholecystostomy tube was removed. The patient recovered uneventfully and is doing well over 9 months later. Conclusion There is no consensus on treatment with options reported ranging from medical management with antibiotic therapy to more invasive procedures such as cholecystostomy tube or cholecystectomy. Less invasive management options are an alternative for Salmonella cholecystitis.